Raised in the Spirit of the Class Struggle: Children, Youth, and the Interwar Ukrainian Left in Canada - Hinther, Rhonda (Labour/Le Travailleur, 2007)
Abstract This paper focuses on the experiences of children and youth who were born into the Ukrainian Labour Farmer Temple Association (ulfta) during the 1920s and 1930s. It examines the priorities of the movement’s parents and male leaders and their efforts to implement activities that would serve to politicize and impart a strong sense of Ukrainianness in youngsters. It also considers the ways in which young people themselves contributed to the shape of the movement. Children and youth, because of their particular positions at specific intersections of class, ethnicity, age, and gender, experienced the ulfta in ways that were distinct from their parents. Because of the ulfta’s emphasis on Ukrainian culture, their childhoods were also significantly different from other socialist children. The movement’s emphasis on Marxist-Leninism and the class struggle also divided these children from their non-socialist Ukrainian and non-Ukrainian peers. By applying an intersectional perspective to the interwar Ukrainian left, this paper also seeks to broaden our understanding of the movement’s connection with the Communist Party of Canada (cpc). The ulfta and the cpc enjoyed a consistently difficult relationship through much of this period, particularly where Ukrainian cultural expression was concerned. An examination of youngsters’ activities illustrates some of the many ways in which the ulfta leaders and rank-and-file members (including the young people themselves) resisted the cpc’s attempts to control the ulfta and its resources.